Teachers’ experiences of developing the teacher-student relationships during COVID-19 in China - Wenling Li; Mohd Mokhtar Muhamad; Fathiyah Mohd Fakhruddin; Weili Zhou; Ruijia Zuo (International Journal of Evaluation and Research in Education (IJERE), 2023)
The purpose of this study was to express middle school teachers’ experiences of developing teacher-student relationships (TSRs) in online teaching during COVID-19 in China. The study used a qualitative phenomenological design to offer an in-depth description of the experience’s teachers perceive as strategies to develop TSRs. Participants (N=6) were from several middle schools in Nanning, GuangXi, China. Information was collected with semi-structured interviews and analyzed using a five-step phenomenological method in mental research. Data analysis revealed five general themes about teachers’ experiences. The study found that teachers’ proactively initiating dialogues, responding to student needs, emotion-based information exchange, treating students with respect, and expressing motivation and expectations for students were the strategies to develop TSRs. The results of this study can be used in middle school to create positive interventions to enhance educators’ understanding of strategies associated with TSRs.